NANOSATELLITE BODY COMPOSITE MATERIAL THERMAL CONDUCTIVITY DETERMINATION COMPUTATIONAL AND THEORETICAL METHOD - S V Reznik; P V Prosuntsov; O V Denisov; N M Petrov; Vonheong Lee (RUDN Journal of Engineering Research, 2017)
In this paper, we present a technique for determining the thermal conductivity of an anisotropic composite material (CM) of a body of nanosatellite on a contact heating installation. A description is given of the technique of a thermal physics experiment with CM samples in the form of thin-walled plates, which were parts of the body of nanosatellite.